2010
DOI: 10.1007/s13312-010-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and cytokines in childhood obesity

Abstract: Development, pathogenesis and complications of childhood obesity consist of complex mechanisms including numerous cytokines and hormones. New treatment modalities depend on understanding these complex mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 66 publications
2
59
0
11
Order By: Relevance
“…Adipokines secreted by visceral adipose tissue are associated with components of metabolic syndrome 4,7,10. Studies on obese children, adolescents and adults have evidenced a direct correlation between leptin and adiposity markers (BMI, WC and BFP) and with glucose, insulin and HOMA-IR values 8,9,34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipokines secreted by visceral adipose tissue are associated with components of metabolic syndrome 4,7,10. Studies on obese children, adolescents and adults have evidenced a direct correlation between leptin and adiposity markers (BMI, WC and BFP) and with glucose, insulin and HOMA-IR values 8,9,34.…”
Section: Discussionmentioning
confidence: 99%
“…An excess of body fat not only results in metabolic changes in adipose tissue and the induction of insulin resistance but also leads to endothelial dysfunction via pro-inflammatory and pro-thrombotic effects due to the action of pro-inflammatory cytokines and adipokines 7. Leptin and adiponectin, which are the primary adipokines produced by adipose tissue, play important roles in the cardiometabolic outcomes associated with excess body weight 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, waist circumference (WC) was not associated with TNF-α concentrations. Arslan et al [11] concluded that TNF-α and IL-6 increased, while IL-10 decreased in obese children.…”
Section: Introductionmentioning
confidence: 99%
“…with many biological activities [21]. Development and complications of obesity causes numerous adipokines, hormones and cytokines takenplace [22].…”
Section: Inhibitory Effect Of Mce On Lipid Content Of Liver In Hfd-fementioning
confidence: 99%